The YouTubers phenomenon: what makes YouTube stars so popular for young people? - Pereira, Sara (2018)
This paper aims to explore and to analyse the channels and the five most viewed videos published in May 2017 by two YouTubers – the Portuguese Wuant and the Swede PewDiePie. These YouTube stars were highlighted by a sample of Portuguese teenagers during the fieldwork of the European research project Transmedia Literacy. Based on these two cases, the article intends to identify the main distinctive traits of their productions, focusing on con-tents, performances and aesthetics, seeking to understand what characteristics make these YouTubers so popular among the young generation. The video analysis reveals complex, hybrid characters whose merit of attracting mil-lions of fans cannot be denied. Their eccentric body language, the preference for easy jokes, the recurrence of slang, and a certain civic apathy are some of the very distinguishing features of these YouTubers.